Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1016/j.juro.2009.01.022
|View full text |Cite
|
Sign up to set email alerts
|

The Bone Anchor Suburethral Synthetic Sling for Iatrogenic Male Incontinence: Critical Evaluation at a Mean 3-Year Followup

Abstract: The bone anchored suburethral synthetic sling is a simple and attractive procedure that can produce immediate good results with low morbidity, especially when strictly selected patients are treated. Radiotherapy remains a strong predictor of failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
8

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 19 publications
1
25
0
8
Order By: Relevance
“…To date, no influence of patients' age on the outcome and complication rates could be identified in MS [14,18,19] or AUS [7] . In this regard, our results are consistent with the present literature of AUS and MS.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no influence of patients' age on the outcome and complication rates could be identified in MS [14,18,19] or AUS [7] . In this regard, our results are consistent with the present literature of AUS and MS.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal cure rates have been reported with the bone-anchored perineal sling and generally range from 39% to 90%, depending on the method of evaluation and definition of success. [77][78][79][80][81][82][83][84] As more experience is gained with this procedure, the importance of patient and material selection is emphasized, as it greatly impacts outcome. In a study of 46 men with a mean follow-up period of 18 months, the procedure was successful in 76%, resulted in improvement in 35%, and failed in 24% of patients due to the use of absorbable graft material.…”
Section: Non-adjustable Male Slingsmentioning
confidence: 99%
“…Outcomes for continence/cure are typically de fi ned as no pad or one dry pad/day with improvements de fi ned in some studies as a decrease in pad use by 50 % [ 196,221 ] . For example, one study of bone-anchored synthetic slings demonstrated a 55 % cure rate at 3 years [ 194 ] . In fact, a reference chart is available to predict the success of bone-anchored perineal sling placement (Fig.…”
Section: Urethral Slingsmentioning
confidence: 99%
“…Complications of suburethral sling placement include infection, urethral erosion, urinary retention, scrotal and perineal numbness, and pelvic pain [ 192,194,223 ] . The quality of life for men following the bulbourethral sling placement generally improves.…”
Section: Urethral Slingsmentioning
confidence: 99%